Halal Sertification, Logistics, and HR on Halal Supply Chain Performance in the Food Industry In Indonesia - Rita (JSE: Jurnal Sharia Economica, 2025)
This study aims to analyze the influence of halal certification, logistics infrastructure, and human resource competencies on the performance of the halal supply chain in the Indonesian food industry. The research is motivated by the increasing awareness of Muslim consumers regarding halal products and the importance of applying Islamic principles throughout the supply chain. A quantitative approach with a causal research design was employed. Data were collected through questionnaires distributed to food industry players whose products have been halal certified, across five major cities. Data analysis was conducted using SmartPLS to assess validity, reliability, and inter-variable relationships. The results indicate that halal certification and logistics significantly and positively affect the performance of the halal supply chain, while human resource competency does not show a significant impact. These findings highlight that compliance with halal standards and efficient logistics systems are key to maintaining the integrity of the halal supply chain, whereas the quality of human resources remains a challenge. This research provides important contributions to the development of sustainable and competitive strategies for the halal food industry in both domestic and global markets.